Local cellular immune response plays a key role in protecting chickens against hepatitis-hydropericardium syndrome (HHS) by vaccination with a recombinant fowl adenovirus (FAdV) chimeric fiber protein - De Luca, Carlotta; Schachner, Anna; Heidl, Sarah; Hess, Michael; Liebhart, Dieter; Mitra, Taniya (Frontiers in Immunology, 2022)
Fowl adenovirus (FAdV)-induced diseases hepatitis-hydropericardium syndrome (HHS) and inclusion body hepatitis (IBH) have been affecting the poultry industry with increasing severity in the last two decades. Recently, a subunit vaccine based on a chimeric fiber protein with epitopes from different fowl adenovirus serotypes (named crecFib-4/11) has been shown to confer simultaneous protection against both HHS and IBH. However, the underlying immune mechanisms in chickens are still enigmatic, especially because of frequently absent neutralizing response despite high levels of protection. In this study, we investigated the kinetics of the humoral and cellular immune responses in specific pathogen-free chickens after vaccination with crecFib-4/11 and/or challenge with a HHS-causing strain, on a systemic level, as well as locally in target and lymphoid organs. The humoral response was assessed via enzyme-linked immunosorbent assay (ELISA) and virus neutralization (VN) test in serum, while the cellular immune response was determined by phenotyping using flow cytometry. Although vaccination induced serum antibodies, as confirmed by ELISA, such antibodies exhibited no pre-challenge neutralizing activity against FAdV-4. Nevertheless, immunized birds experienced a significant B cell increase in the liver upon challenge, remaining high throughout the experiment. Furthermore, vaccination stimulated the proliferation of cytotoxic T lymphocytes, with earlier circulation in the blood compared to the challenge control and subsequent increase in liver and spleen. Overall, these findings imply that protection of chickens from HHS after crecFib-4/11 vaccine relies on a prominent local immune response in the target organs, instead of circulating neutralizing antibodies.